Lithuanian Sign Language Poetry: Location as Mean of Expression of Metaphors - Teresė, Anželika (Taikomoji kalbotyra, 2022)
In order to solve issues in sign language linguistics, address matters pertaining to maintaining high quality of sign language (SL) translation, contribute to dispelling misconceptions about SL and deaf people, and raise awareness and understand of the deaf community heritage, this article, for the first time in a Lithuanian scientific journal, discusses authentic poetry in Lithuanian Sign Language (LSL) and inherent metaphors that are created by using the phonological parameter – location. The study covered in this article is twofold, involving both the micro-level analysis of metaphors in terms of location as a sub-lexical feature and the macro-level analysis of the poetic context. Cognitive theories underlie research of metaphors in sign language poetry in a range of sign languages. The study follows this practice. In view of the abovementioned reasons, this piece of research is new and relevant to Lithuania. The article covers qualitative analysis of 10 pieces of LSL poetry. The analysis employs ELAN software widely used in sign language research. The target is to examine how specific types of location are used for the creation of metaphors in LSL poetry and what metaphors are created. The results of the study show that LSL poetry employs a range of locations resulting in a host of metaphors created by using classifier signs and by modifying the location of the established signs. The study also reveals that LSL poetry mostly tends to create reference metaphors indicating status and power. As the study shows, LSL poets metaphorically encode status by encoding another meaning in the same sign, which results in creating double metaphors. The metaphor of identity has been determined to consist of chest signing. Notably, the poetic context has revealed that the latter metaphor can also be identified as a metaphor of life. The study goes on to note that deaf poets create metaphors related to the importance of various phenomena, significance of the lyrical subject. Notably, the study has allowed detecting locations never mentioned in previous SL research as used for the creation of metaphors. For instance, previous SL research fails to cover temporal metaphors expressed by signing in central and peripheral areas and attitudinal metaphors represented by signing near the eye. The study has also detected a sign that can be identified as a metaphor of death and that is absent in previous SL research.
Keywords: lithuanian sign language; sign language poetry; sign language metaphors; phonological level; location